Adsorption of silver ion from the aqueous solution using a polyvinylidene fluoride functional membrane bearing thiourea groups. (April 2020) - Liu, Pei; Wang, Xiuli; Tian, Lei; He, Benqiao; Lv, Xiaolong; Li, Xida; Wang, Cai; Song, Laizhou
Highlights: Thiourea groups were grafted to PVDF molecular chains for the adsorption of Ag(I). The fabricated TU-PVDF membrane shows an excellent affinity to Ag(I). With the presence of disturbances, TU-PVDF membrane can still capture Ag(I). The reused property of fabricated TU-PVDF membrane is promising. Black silver and Ag2 S particles can be harvested during the desorption process. Abstract: A novel polyvinylidene fluoride (PVDF)-based functional membrane was fabricated with the incorporation of thiourea groups for removal of Ag(I) from the aqueous solution. The morphology, hydrophilicity, chemical groups and components of the membrane were characterized, and its trapping performance of Ag(I) was evaluated. Effects of conventional parameters (such as pH and initial Ag(I) concentration) on Ag(I) uptake and the adsorption characteristics were investigated. The adsorption equilibrium can be obtained about 6 h with a removal efficiency of 99 % for this metal. The adsorption kinetic and isotherm adsorption of Ag(I) can be described by the pseudo-second-order equation and the Langmuir model; the breakthrough curves can be described by Thomas model. This process exhibits the spontaneous and exothermic nature. The coexisting substances decrease the Ag(I) uptake, Co(II) and Na2 S2 O3 show a more remarkable disturbance than Cu(II), Ni(II), TA, and EDTA. The analysis of adsorption-diffusion equations ascertains the distribution gradient of Ag(I) along the longitudinal filtration direction of the membrane stack. This membrane shows a noticeable antifouling property and an excellent reusability (< 4.15 % loss in Ag(I) uptake over 8 runs). The eluent (0.3 mol L −1 thiourea and 0.1 mol L −1 HNO3 mixed solution) can be reused without apparent loss in regeneration performance after 8 cycles. In addition, a promising issue should be noted that the black silver and silver sulfide particles can be harvested during the regeneration process.